Nexus between uncertainty, remittances, and households consumption: Evidence from dynamic SUR application - Yin, Ying; Qamruzzaman, Md.; Xiao, He; Mehta, Ahmed Muneeb; Naqvi, Farah Naz; Baig, Imran Ali (Frontiers in Environmental Science, 2022)
Household consumption induces aggregated economic activities by pushing market demand, capital accumulation and financial growth in the economy; on the other hand, instability in household consumption adversely affects the overall economic progress. Thus, exploring the key determinants responsible for household consumption instability is essential. The motivation of the study is to gauge the role of pandemic uncertainties and remittance inflow on household consumption in lower, Lower-middle, and Upper-Middle-income Countries for the period 1996 to 2020. The study employed several econometrical tools, including a panel cointegration test with the error correction term, dynamic SUR. The panel unit root test following CADF and CIPS documented variables are stationary after the first difference, and long-run associations are confirmed with the panel cointegration test. The coefficient of Dynamic Seemingly Unrelated Regression exposed pandemic uncertainties and has a negative impact on household consumption in all three-panel estimations; however, the coefficient of PUI is more prominent with COVID-19 effects. Remittances’ role in household consumption was positive and statistically significant, suggesting migrant remittances encourage additional consumption among households. On the policy aspect, the study proposed that the government should undertake macro policies to manage policy uncertainties so that the normal course of consumption level should not be interrupted because household consumption volatility creates discomfort in aggregated development. Moreover, efficient reallocation and remittance channels should be ensured in the economy; therefore, efficient institutional development has to be confirmed.